1995
DOI: 10.1038/378776a0
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and increased generation of reactive oxygen species in Down's syndrome neurons in vitro

Abstract: Down's syndrome (DS) or trisomy 21 is the most common genetic cause of mental retardation. Development of the DS brain is associated with decreased neuronal number and abnormal neuronal differentiation, and adults with DS develop Alzheimer's disease. The cause of the neurodegenerative process in DS is unknown. Here we report that cortical neurons from fetal DS and age-matched normal brain differentiate normally in culture, but DS neurons subsequently degenerate and undergo apoptosis whereas normal neurons rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
403
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 698 publications
(426 citation statements)
references
References 24 publications
20
403
0
3
Order By: Relevance
“…Alterations in chromosome number, particularly trisomy 21, have been associated with elevated mitochondrial ROS, oxidative damage, diminished metabolism, and compromised resilience (Busciglio & Yankner, 1995; Coskun et al, 2016; Slonim et al, 2009; Zis et al, 2012) Here, we show that human DS HF and mouse Dp16 MEF display compromised mitochondrial function, oxidative stress, and activated Nrf2 antioxidant response. Furthermore, our results demonstrate that sustained Nrf2 stabilization is vital to maintain cell function in both DS and Dp16.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Alterations in chromosome number, particularly trisomy 21, have been associated with elevated mitochondrial ROS, oxidative damage, diminished metabolism, and compromised resilience (Busciglio & Yankner, 1995; Coskun et al, 2016; Slonim et al, 2009; Zis et al, 2012) Here, we show that human DS HF and mouse Dp16 MEF display compromised mitochondrial function, oxidative stress, and activated Nrf2 antioxidant response. Furthermore, our results demonstrate that sustained Nrf2 stabilization is vital to maintain cell function in both DS and Dp16.…”
Section: Discussionmentioning
confidence: 48%
“…An expanding number of studies have reported the presence of chronic oxidative stress and mitochondrial dysfunction in DS at both the cellular and organismal levels (Annerén & Epstein, 1987; Busciglio & Yankner, 1995; Antonarakis et al, 2004; Lott & Dierssen, 2012; Campos et al, 2011). Recently, we reported that decreased mitochondrial activity, increased ROS and mitochondrial fragmentation in DS cells are associated with transcriptional activation of the nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) signaling pathway (Helguera et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ROS-mediated cell death may be important in the pathogenesis of several neurodegenerative disorders (Coyle and Puttfarrcken, 1993;Busciglio and Yankner, 1995). Moreover, oxidative tissue injury has been observed to be central in reperfusion injury of ischaemic tissues in myocardium, kidney and brain (Bulkley, 1983).…”
mentioning
confidence: 99%
“…Furthermore, serum IL-8 levels were markedly elevated in Patient 1. Oxidative stress is important in DS pathology, and reactive oxygen species (ROS) levels are important for IL-8 expression (Busciglio and Yankner 1995;Ko et al 2014). Neutrophils are effector cells that kill bacteria or destroy affected tissues, predominantly through ROS production.…”
Section: Discussionmentioning
confidence: 99%